Juventude e ensino superior: impactos da inserção universitária na vida de estudantes de classes populares - Valdete Côco; Letícia Cavassana Soares; Nelma Suely Bragança; Raiane Lóss Cardoso (EccoS – Revista Científica)
In the struggle for the democratization of school, we are experiencing a context of affirmation of education as a right, reflected on the policies that aim the increase in the offering and the proposal of programs to support students’ stay in the school systems. Thus, this study addresses the impacts on underprivileged class students lives when they enroll in an undergraduate program and decide to take part of the Educational Tutorial Program Knowledge Connections: Education Project. Based on Bakhtin’s studies, we explored impressions of the beginning of students’ college lives considering their expectations, challenges, possibilities and perspectives, in conjunction with the development of a qualitative research entitled Trajectories of Students. Taking memorials produced by students as a source, we noticed that the undergraduate students broaden their social webs, urging new learning opportunities. The difficulties, the overcomes and achievements dialogue with students’ connection to the university and the program, relating to the investment on the underprivileged students educational initiatives.